COVID-19 in Africa: an ovarian victory? - Dufailu, Osman A.; Afriyie-Asante, Afrakoma; Gyan, Bernard; Kwabena, David A.; Yeboah, Helena; Ntiakoh, Frank; Asare-Werehene, Meshach (Université d'Ottawa | University of Ottawa, 2021)
Abstract Coronavirus disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) mainly attacks the respiratory system and is characterized by pneumonia, cytokine storm, coagulation disorders and severe immune downregulation. Although public health experts predicted worst outcomes in Africa, the incidence, hospitalization and mortality rates have been lower in Africa compared to other continents. Interestingly, lower incidence and mortality rates have been observed in women from Africa compared to their cohorts from other continents. Also, in the US non-Hispanic Black females have lower COVID-19 and death rates compared to their white counterparts. It’s unclear why this significant difference exists; however, the ovarian function, genetics and immunological statuses could play a major role. Women of African descent have elevated levels of estrogen compared with Caucasians hence we anticipate that estrogen might offer some protection against the SARS-CoV-2 infections. The racial differences in lifestyle, age and inaccessibility to contraceptive usage might also play a role. Here, we provide insight on how the high levels of estrogen in African women might contribute to the lower cases and fatalities in Africa. Specifically, estrogen might offer protection against COVID-19 by suppressing hyper-production of cytokines, promoting anti-inflammatory cytokines, stimulating antibody production and suppressing endoplasmic reticulum (ER) stress. This will as well provide useful information on how future pandemics could be managed using Africa as a case study.